Research Priorities for Plasma and Platelet Transfusion Strategies in Critically Ill Children: From the Transfusion and Anemia EXpertise Initiative–Control/Avoidance of Bleeding. (January 2022) - Nellis, Marianne E.; Remy, Kenneth E.; Lacroix, Jacques; Cholette, Jill M.; Bembea, Melania M.; Russell, Robert T.; Steiner, Marie E.; Goobie, Susan M.; Vogel, Adam M.; Crighton, Gemma; Valentine, Stacey L.; Delaney, Meghan; et al.
Abstract : Objectives: To present a list of high-priority research initiatives for the study of plasma and platelet transfusions in critically ill children from the Transfusion and Anemia EXpertise Initiative–Control/Avoidance of Bleeding. Design: Systematic review and consensus conference of international, multidisciplinary experts in platelet and plasma transfusion management of critically ill children. Setting: Not applicable. Patients: Critically ill pediatric patients at risk of bleeding and receiving plasma and/or platelet transfusions. Interventions: None. Measurements and Main Results: A panel of 13 experts developed research priorities for the study of plasma and platelet transfusions in critically ill children which were reviewed and ratified by the 29 Transfusion and Anemia EXpertise Initiative–Control/Avoidance of Bleeding experts. The specific priorities focused on the following subpopulations: severe trauma, traumatic brain injury, intracranial hemorrhage, cardiopulmonary bypass surgery, extracorporeal membrane oxygenation, oncologic diagnosis or stem cell transplantation, acute liver failure and/or liver transplantation, noncardiac surgery, invasive procedures outside of the operating room, and sepsis and/or disseminated intravascular coagulation. In addition, tests to guide plasma and platelet transfusion, as well as component selection and processing, were addressed. We developed four general overarching themes and 14 specific research priorities using modified Research and Development/University of California, Los Angeles methodology. Conclusions: Studies are needed to focus on the efficacy/harm, dosing, timing, and outcomes of critically ill children who receive plasma and/or platelet transfusions. The completion of these studies will facilitate the development of evidence-based recommendations.